Large Duodenal Gastrointestinal Stromal Tumor Presenting with Acute Bleeding Managed by a Whipple Resection. A Review of Surgical Options and the Prognostic Indicators of Outcome - Machado, Norman Oneil; Chopra, Pradeep J; Al-Haddabi, Ibrahim Hassan; Al-Qadhi, Hani (JOP. Journal of the Pancreas, 2011)
Context Duodenal gastrointestinal stromal tumors (GISTs) are uncommon and constitute a relatively small subset of GISTs which presents a unique dilemma having various surgical options. A case of a large ulcerating duodenal GIST arising from the second and third parts of the duodenum and involving the pancreas which was managed by a Whipple resection is presented. The literature is also reviewed to present the current status on surgical options, outcome, prognostic indicators and the role of imatinib mesylate in its management. Case report A 58-year-old patient presented with acute gastrointestinal bleeding which was diagnosed to be due to a duodenal GIST following CT scan and endoscopic biopsy. The mass which measured about 10x9 cm originated from the 2nd part and extended into the 3rd part of the duodenum. He underwent a Whipple resection, and histopathology confirmed a duodenal GIST having a greater than 10 mitotic count per fifty high power field and areas of necrosis. Postoperatively, he received imatinib mesylate 400 mg bid; however, 4 months later, he presented with multiple disseminated peritoneal metastases and succumbed to the disease 2 months later. Conclusion GISTs of the duodenum which are small in size and do not involve the papilla of Vater are better resolved using a limited resection of the duodenum since the outcome in terms of operative risk or disease recurrence is not influenced in these cases. However, large tumors with more extensive involvement would require a pancreaticoduodenectomy to achieve adequate tumor clearance. Even though duodenal GISTs have a relatively better prognosis as compared to GISTs at other sites, their aggressiveness ranges from small indolent tumors to aggressive sarcomas. Following tumor resection, a recurrence rate of about 40% has been reported. A more favorable prognosis in duodenal GISTs is attributed to a lower prevalence of P53 loss, the duodenal location of the tumor, a smaller size of the lesion and a low mitotic count. Imatinib mesylate is reported to play a role in neoadjuvant therapy as well as in the management of metastatic and recurrent disease, although some of these tumors may fail to respond. Image: Specimen after Whipple resection revealing a large duodenal GIST tumor.